Tuberkulosis Kutis Verukosa: Laporan Kasus yang tidak Terdiagnosis Selama 20 Tahun - Alfadli, Robby; Khairunisa, Sasa (Faculty of Medicine, Universitas Andalas, 2025)
Cutaneous tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. One form of cutaneous tuberculosis that is rare and often difficult to diagnose is Verrucous Cutaneous Tuberculosis (VCTB). This case report aims to describe the clinical presentation, diagnosis and management of VCTB in a delayed patient receiving appropriate therapy. It has been reported a 32-year-old man presented with a painful verrucous rash and yellowish discharge on his left thigh that has lasted for 20 years. The patient had a history of trauma at the lesion site and had received topical and oral therapy, but did not show satisfactory results. Physical examination and histopathology confirmed the diagnosis of VCTB. The patient was treated with antituberculosis drugs for six months and experienced significant clinical improvement. VCTB is often challenging to diagnose because of its non-specific clinical manifestations and similarity to other skin diseases. Delay in diagnosis and therapy may worsen the prognosis and increase the risk of complications. The VCTB diagnosis is based on a combination of history, physical examination, histopathological examination, and other supporting tests. Treatment for VCTB is the same as pulmonary tuberculosis, namely with antituberculosis drugs for six months. VCTB needs to be considered in diagnosis because many clinical verrucous rashes resemble this disease, especially in patients with a history of trauma and inadequate response to therapy. Keywords: antituberculosis, rash, verrucous cutaneous tuberculosis